2010
DOI: 10.1007/s11606-010-1605-5
|View full text |Cite
|
Sign up to set email alerts
|

A Video-Intervention to Improve Clinician Attitudes Toward Patients with Sickle Cell Disease: The Results of a Randomized Experiment

Abstract: Our results suggest that the attitudes of clinicians toward sickle cell patients may be improved through a short and relatively easy to implement intervention. Whether the attitudinal differences associated with our intervention are sustainable or are linked to clinical outcomes remains to be seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 33 publications
1
95
0
Order By: Relevance
“…11 Haywood et al's study 12 was designed to test a video intervention on clinician attitudes towards patients with sickle-cell disease by using a scale of clinician attitudes towards positive and negative patient behaviors. To create the scale, clinicians rated examples of a range of patient behaviors; a history of AMA discharges was considered as negative "red-flag" behavior.…”
Section: Stigma and Ama Dischargesmentioning
confidence: 99%
“…11 Haywood et al's study 12 was designed to test a video intervention on clinician attitudes towards patients with sickle-cell disease by using a scale of clinician attitudes towards positive and negative patient behaviors. To create the scale, clinicians rated examples of a range of patient behaviors; a history of AMA discharges was considered as negative "red-flag" behavior.…”
Section: Stigma and Ama Dischargesmentioning
confidence: 99%
“…15 Examples of these negative attitudes are found in reports of adult patients with SCD that health care providers fail to show them respect by stigmatizing them as being "drug-seeking," that providers often lack trust in them by expressing doubts about the veracity of the patient' s reports of their pain experience, and that providers do not treat the patient with SCD with a caring approach. 15,23 Although formal studies of these attitudes and experiences among youth with SCD are much more limited in number, the studies that can be identified document many of the same issues, 24 and they comport with the experiences of youth with SCD who we talk to and care for in our own professional practices. Furthermore, parents of hospitalized children with SCD report many of the same difficulties in their experiences and relationships with health care providers as reported by adult patients.…”
mentioning
confidence: 99%
“…We posit use of multimedia tools to prompt individual reflective writing exercises. For example, Haywood et al (2010) use a film highlighting experiences of patients with sickle cell disease (SCD) receiving pain control treatment. They found the intervention (even without a written reflection component) reduced negative and increased positive attitudes toward patients with SCD (Haywood et al 2010).…”
Section: A Broader Basis For Teaching Reflectionmentioning
confidence: 99%
“…For example, Haywood et al (2010) use a film highlighting experiences of patients with sickle cell disease (SCD) receiving pain control treatment. They found the intervention (even without a written reflection component) reduced negative and increased positive attitudes toward patients with SCD (Haywood et al 2010). Using multimedia for introspection serves as a launching point for collaborative group reflection and can push students to more nuanced and organic discussions with peers.…”
Section: A Broader Basis For Teaching Reflectionmentioning
confidence: 99%